1996
DOI: 10.1021/ja953858a
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Isomerizations and Oxygen Atom Loss in Formaldehyde and Acetaldehyde Carbonyl Oxides. A Theoretical Investigation

Abstract: The lowest singlet and triplet potential energy surfaces of formaldehyde carbonyl oxide (1) and acetaldehyde carbonyl oxide (2) have been investigated in the regions concerning the most relevant unimolecular reactions by means of CASSCF and MRDCI ab initio quantum-chemical calculations. The questions related to the mechanism of O-atom loss from carbonyl oxides, as well as the competition between the cyclization to dioxirane and the tautomerization to hydroperoxide in methyl-substituted carbonyl oxides are addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
180
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(209 citation statements)
references
References 94 publications
26
180
3
Order By: Relevance
“…[ 13] The geometric parameters of the transition structure (TS4 in Figure 3) for the concerted POZ decomposition agree qualitatively with other theoretical results [14,75] except for the O1 ± O5 bond length, which is predicted by the CASSCF approach to be more than 0.3 longer. The computed activation energy at 0 K is 21.7 kcal mol À1 (18.7 kcal mol À1 taking into account the ZPVE corrections) is also comparable with other results from the literature [14] (Figure 2).…”
supporting
confidence: 83%
“…[ 13] The geometric parameters of the transition structure (TS4 in Figure 3) for the concerted POZ decomposition agree qualitatively with other theoretical results [14,75] except for the O1 ± O5 bond length, which is predicted by the CASSCF approach to be more than 0.3 longer. The computed activation energy at 0 K is 21.7 kcal mol À1 (18.7 kcal mol À1 taking into account the ZPVE corrections) is also comparable with other results from the literature [14] (Figure 2).…”
supporting
confidence: 83%
“…65,66 Anglada et al investigated with theory the ozonolysis of ethene 86 and the unimolecular isomerization and loss of an O-atom from CH 2 OO and CH 3 CHOO. 87 They concluded that energetic CH 2 OO can decompose to HCO + OH and O( 3 P) + H 2 CO or isomerize to dioxirane that isomerizes further to methylenebis(oxy). Methylenebis(oxy) decomposes to CO 2 + H 2 (or 2H) or isomerizes further to formic acid and decomposes to H 2 O + CO and CO 2 + H 2 .…”
Section: A Stabilization Vs Decompositionmentioning
confidence: 99%
“…Larger and more complex conformers such as heterosubstituted or cyclic structures are subject to additional unimolecular rearrangements (Vereecken and Francisco, 2012). On the unimolecular decomposition rates and products few experimental data are available (Horie et al, 1997(Horie et al, , 1999Fenske et al, 2000a;Novelli et al, 2014b;Kidwell et al, 2016;Fang et al, 2016a;, but more is available from theoretical studies explicitly focusing on the path followed by different conformers (Anglada et al, 1996;Aplincourt and Ruiz-López, 2000;Kroll et al, 2001;Zhang and Zhang, 2002;Nguyen et al, 2009b;Kuwata et al, 2010).…”
mentioning
confidence: 99%